2020
DOI: 10.47153/jbmr14.422020
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Career Development, Work-Family Conflict, and Job Satisfaction on Millennials’ Turnover Intention in Banking Industry

Abstract: With a strong domination of the Millennials generation in the workforce, they become one of the key holders in the success of the organisation and the economy. Their behaviour of working short tenure and job-hop worries many organisations as this halt the organisations’ growth, performance and productivity while also incurring extra costs. Banking sector is known to have a high turnover rate and has been lacking in the number of talents which delays their implementation on key strategic initiatives. It becomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Previous literature has clearly identified that WFC has predominant impacts on intention to quit (Mumu et al, 2021). Elian et al (2020) have also found that WFC has a significant positive direct impact on Turnover Intention of Millennial generation in the banking industry.…”
Section: Work-family Conflict and Turnover Intentionmentioning
confidence: 87%
“…Previous literature has clearly identified that WFC has predominant impacts on intention to quit (Mumu et al, 2021). Elian et al (2020) have also found that WFC has a significant positive direct impact on Turnover Intention of Millennial generation in the banking industry.…”
Section: Work-family Conflict and Turnover Intentionmentioning
confidence: 87%
“…Dominating conflict behavior is considerably responsible not just for an escalating conflict on the other hand they also for hindering collaboration and interaction (Ho & Yeung., 2020). Elian et al (2020) found that dominating conflict behavior is positively related to turnover intentions, meaning that employees who experience dominating conflict behavior are more likely to have intentions to leave the organization. Hence it is proposed that beyond immediate self-interests through idealized influence (charisma), inspiration, intellectual stimulation, or individualized consideration" (Bass, 1999).…”
Section: H1: Problem-solving Behavior Is Positively Related To Work E...mentioning
confidence: 97%
“…Career growth pertains to the formal evaluation employed by companies and organizations to assess the availability of skilled employees who fulfill the necessary job requirements. Previous research has indicated that employee's career growth positively impacts employees (Elian et al, 2020) and decreases employee turnover intention (Manthi et al, 2018). Studies conducted in Maldives have demonstrated that positive perceptions of career development practices significantly and positively affect employee retention (Imna et al, 2015).…”
Section: Career Growth As Moderator Between Job Performance Job Satis...mentioning
confidence: 99%